Multicenter prospective observational study on hospital pharmacist interventions to reduce inappropriate medications - Suzuki, Shinya; Uchida, Mayako; Sugawara, Hideki; Suga, Yukio; Nakagawa, Takayuki; Takase, Hisamitsu (Frontiers in Pharmacology, 2023)
Background: In Japan, the involvement of hospital pharmacists in inappropriate medicines (IMs) practices has not been sufficiently reported. Therefore, this prospective study described the interventions of hospital pharmacists in discontinuing inappropriate drugs or reducing drug doses.We conducted a prospective, multicenter, observational study to investigate the intervention of hospital pharmacists in inappropriate prescriptions for inpatients in September 2018. Fifty pharmacists from 45 hospitals in Japan participated in this study. IMs were defined as medications that pharmacists deemed inappropriate for patient treatment. The subjects of the study were patients who interacted with the participating pharmacists.Results: During the study period, the median number of beds in hospitals where the 50 participating pharmacists worked was 380, and the average number of beds for which the pharmacists were responsible was 49. The enrolled hospital pharmacists recommended that doctors discontinue or reduce the doses of their regular drugs for 347 out of 1,415 (24.5%) patients. Among the 391 pharmacists' recommendations to reduce IMs for 347 patients, physicians accepted 368 (94.1%) recommendations, and 523 drugs were discontinued as a result. Pharmacist intervention also led to improvements in hypnotic sedation, delirium, and hypotension. The most common reasons for IMs identified by pharmacists were "long-term administration of irresponsible or aimless medications" (44.5%), "adverse effects caused by medications" (31.5%), and "medications-mediated duplication of the pharmacological effect" (15.3%). Approximately 90% of pharmacists' suggestions to reduce medications were accepted for each reason. The average number of regular medications used by patients involved in drug reduction was 8.2, and the average number of medications reduced was 1.7. A sub-analysis showed that patients using opioids tended to take more medications and were more depressed. Interventions by pharmacists certified in palliative pharmacies tended to reduce adverse drug events.This was the first multicenter prospective observational study conducted in Japan to demonstrate hospital pharmacist intervention's effectiveness in promoting appropriate prescription and, consequently, a reduction in the number of medications in use and polypharmacy.